Pro-health activity of dandelion (Taraxacum officinale L.) and its food products – history and present. (August 2019) - Lis, Bernadetta; Olas, Beata
Graphical abstract: Highlights: Dandelion ( Taraxacum officinale L.) as a source of nutrients, minerals and vitamins. T. officinale L. is a plant with multidirectional health effects. Flavonoids, phenolic acids and terpenes may lower the risk of health disorders. Different organs from dandelion can be consumed as syrup, tea, coffee, wine, etc. Abstract: Since ancient times, dandelion ( Taraxacum officinale L.) has been consumed in various forms as a valuable source of nutrients, minerals and vitamins which can also have beneficial effects on various complex diseases. It is described as a nontoxic herb with exceptional biological activity. The aim of this review is to present the multidirectional activity of various dandelion products whose dietary intake may help to prevent, or reduce the risk of, the development of a range of diseases, including cancer, obesity, hepatitis, arthritis and cardiovascular disease. In addition, the paper describes the history of dandelion usage and serves as an overview of current literature based on in vitro and in vivo studies. However, the correlation between the chemical content and the biological properties of dandelion and its food products are not always clear, and further experiments are required to determine the therapeutic doses of dandelion products for use in future research.